Peritoneal Cavity Regulatory B Cells (B10 Cells) Modulate IFN-γ(+)CD4(+) T Cell Numbers During Colitis Development in Mice - Maseda, Damian (2013)
The spleen regulatory B cell subset with the functional capacity to express IL-10 (B10 cells) modulates both immune responses and autoimmune disease severity. However, the peritoneal cavity also contains relatively high frequencies of functionally-defined IL-10-competent B10 cells. In this study, peritoneal cavity B10 cells shared similar cell surface phenotypes with their spleen counterparts. However, peritoneal cavity B10 cells were 10-fold more frequent among B cells than occurred within the spleen, intestinal track or mesenteric lymph nodes and were present at higher proportions among the phenotypically-defined peritoneal B1a>B1b>B2 cell subpopulations. The development or localization of B10 cells within the peritoneal cavity was not dependent on the presence of commensal microbiota, T cells, IL-10 or B10 cell IL-10 production, or differences between their fetal liver or adult bone marrow progenitor cell origins. The BCR repertoire of peritoneal cavity B10 cells was diverse, as occurs in the spleen, and predominantly included germline-encoded V(H) and V(L) regions commonly found in either the conventional or B1 B cell compartments. Thereby, the capacity to produce IL-10 appears to be an intrinsic functional property acquired by clonally diverse B cells. Importantly, IL-10 production by peritoneal cavity B cells significantly reduced disease severity in spontaneous and induced models of colitis by regulating neutrophil infiltration, colitogenic CD4(+) T cell activation and pro-inflammatory cytokine production during colitis onset. Thus, the numerically small B10 cell subset within the peritoneal cavity has regulatory function and is important for maintaining homeostasis within gastrointestinal tissues and the immune system.